1982
DOI: 10.1095/biolreprod26.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Partial Characterization of Two Bovine Pregnancy-Specific Proteins12

Abstract: Two pregnancy-specific proteins were detected by immunoelectrophoresis using antisera developed to homogenates of bovine extraembryonic membranes. Antisera also reacted to extracts of endometrium from pregnant cows and extraembryonic fluids. However, antisera did not react with a preparation presumed to be bovine placental lactogen, fetuin, extracts of various somatic tissues from pregnant cows or extracts of endometrium from nonpregnant cows. One of the proteins had an estimated molecular weight of 65,000-70,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
7

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 21 publications
0
108
0
7
Order By: Relevance
“…The first member of the family was described by Butler et al [1] and was given initially the name pregnancy specific protein B (PSPB) in bovine placenta. Subsequent work by other research groups identified related proteins, which were given names such as PAGs [2,3], 60 kDa -pregnancy serum protein (PSP60) [4], or SBU3 [5] in ruminant ungulates (see Sect.…”
Section: Identification History and Evolutionary Conservation Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…The first member of the family was described by Butler et al [1] and was given initially the name pregnancy specific protein B (PSPB) in bovine placenta. Subsequent work by other research groups identified related proteins, which were given names such as PAGs [2,3], 60 kDa -pregnancy serum protein (PSP60) [4], or SBU3 [5] in ruminant ungulates (see Sect.…”
Section: Identification History and Evolutionary Conservation Of The mentioning
confidence: 99%
“…However, the production of polyclonal and monoclonal antisera requires species-specific antigens, thus harvesting various placental PAG proteins. Initially, anti-PAG sera were produced against semi-purified chorionic antigens, then the obtained semi-specific antisera were purified by adsorption with various bovine tissues harvested from nonpregnant animals [1]. Later, a few potential protein sources were utilised for production of placental antigens (Tab.…”
Section: Identification Of the Pag Proteinsmentioning
confidence: 99%
“…They were purified from cattle placentae and are also found in the maternal blood serum soon after embryo implantation [3]. These glycoproteins were later proven to be closely related to bovine PSPB (Pregnancy Specific Protein B) [4], isolated as early as 1982 by Butler et al [5]. In sheep, PAG called ovPAG [2], SBU-3 [6], or oPSPB [7] were identified mainly by three different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Another signal of pregnancy in the serum is PSPB (pregnancy specific protein B). This has been partially characterized in cattle by Butler et al (1982) (Crock et al, 1988). Radioimmunoassay (RIA) of PSPB enables the course of the pregnancy or late embryonic mortality to be studied (Humblot et al, 1988a, b) (Zoli et al, 1992a).…”
mentioning
confidence: 99%